2011
DOI: 10.1111/j.1551-2916.2011.04793.x
|View full text |Cite
|
Sign up to set email alerts
|

Nb‐Doped 0.9BaTiO3–0.1(Bi0.5Na0.5)TiO3 Ceramics with Stable Dielectric Properties at High Temperature

Abstract: Nb‐doped 0.9BaTiO3–0.1Bi0.5Na0.5TiO3 (0.9BT–0.1BNT) ceramics were prepared by conventional solid‐state method. The dielectric and the structural properties were investigated. It was found that the temperature–capacitance characteristics greatly depended on Nb2O5 content. With the addition of 2.0 mol% Nb2O5, 0.9BT–0.1BNT ceramic sample could satisfy the EIA X9R specification. This material was promising for high‐temperature MLCC application. Microstructure element distribution was studied using TEM and EDS. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…This observation is in accord with those reported in the literature [25,26]. In addition, the peaks corresponding to BaTiO3 in the XRD patterns shifted to lower angles due to the incorporation of the smaller ions Na into Ba sites leads to strengthened Ti-O bonds, and more energy is needed to maintain the balance of Ti 4+ displacement in the TiO6 octahedrons; thus, Tc increased [14,15,19]. The dielectric constant of (1 − x)BaTiO3-x(Bi0.5Na0.5)TiO3 at 25 °C decreased from 2066 to 677 while the tanδ value increased from 2.9% to 3.5% as the x value increased from 0.05 to 0.2.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This observation is in accord with those reported in the literature [25,26]. In addition, the peaks corresponding to BaTiO3 in the XRD patterns shifted to lower angles due to the incorporation of the smaller ions Na into Ba sites leads to strengthened Ti-O bonds, and more energy is needed to maintain the balance of Ti 4+ displacement in the TiO6 octahedrons; thus, Tc increased [14,15,19]. The dielectric constant of (1 − x)BaTiO3-x(Bi0.5Na0.5)TiO3 at 25 °C decreased from 2066 to 677 while the tanδ value increased from 2.9% to 3.5% as the x value increased from 0.05 to 0.2.…”
Section: Resultssupporting
confidence: 81%
“…The microstructures of the fracture surfaces indicated that all fractures were transgranular mode and revealed the presence of very little porosity. Figure 3a,b show the sintered surface and fracture surface of the pure 0.9BaTiO3-0.1(Bi0.5Na0.5)TiO3 ceramic sintered at 1215 °C, which included fine equiaxed grains with an average grain size of 0.57 μm and rod-like grains with a size of approximately 3.2 μm, similar to those reported in the literature [14]. The microstructures of the sintered surfaces and fracture surfaces of the 0.9BaTiO3-0.1(Bi0.5Na0.5)TiO3 ceramics with 1.0 and 2.0 mol% Ta2O5 sintered at 1215 °C are shown in Figure 3c,d, and in Figure 3e,f, respectively.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations